Exploring Students’ Perceptions of Padlet as a Digital Tool for Writing in EFL Higher Education - Lestari, Ika Wahyuni (Universitas Negeri Semarang, 2025)
Grounded in sociocultural theory and the process-oriented approach to writing, this study investigates university students’ attitudes toward Padlet as a tool for supporting English writing in higher education. Data were gathered from 26 students in an Indonesian English Language Education program through online questionnaires combining Likert-scale and open-ended items. Descriptive statistics and thematic analysis were applied. Findings indicate that students perceived Padlet as accessible, easy to use, and motivating, reporting that it increased their attention to grammar and vocabulary, enhanced accuracy, and encouraged regular writing practice. Qualitative results highlighted four main contributions of Padlet activities: fostering awareness of accuracy, improving language mastery, creating a collaborative and enjoyable learning atmosphere, and promoting sustained writing engagement. These findings suggest that Padlet can serve as a mediational tool for socially supported and process-oriented writing instruction. The study contributes to international discussions on technology-enhanced language learning by providing evidence from an EFL higher-education context and underscores the pedagogical potential of digital platforms to integrate collaboration, motivation, and skill development in writing instruction.